THE CORRELATION OF KNOWLEDGE AND THE ANEMIA INCIDENT OF PREGNANT WOMEN IN THE GROGOL HEALTH CENTER, SUKOHARJO REGENCY - Sugiarsih Yusuf, Dian; Prastyoningsih, Aris; Eka Widyastuti, Deny (Journal of Advanced Nursing and Health Sciences, 2025)
The occurrence of anemia in pregnancy causes premature birth, miscarriage, growth and development disorders, and is prone to illness. Anemia in pregnancy is determined by the knowledge factor of pregnant women about anemia. The study objective was determined the correlation of knowledge with the occurrence of anemia in pregnant women at the Grogol Health Center. The study applied observational research through a cross-sectional design. The study sample included 52 pregnant women at the Grogol Health Center. The study used primary and secondary data. The research tool used a questionnaire. Data were analyzed univariately and bivariately. Bivariate analysis applied the Spearman rank. Data analysis showed 1) The characteristics of respondents were high school (65.4%), housewives (51.9%), pregnant in the second trimester (44.2%), and multiparous (51.9%). 2) The level of knowledge of respondents was included in the good category. 3) The majority of pregnant women at the Grogol Health Center did not experience anemia. 4) There was a relationship between the knowledge level and anemia (sig. value 0.014 â‰¤ 0.05). The conclusion that there is a relationship between the knowledge level and anemia at the Grogol Health Center.